Novel Mutations Conferring Amoxicillin Resistance in Helicobacter pylori in South Korea - Soon Young Park; Eun Hwa Lee; Dokyun Kim; Young Goo Song; Su Jin Jeong (Antibiotics, 2023)
Helicobacter pylori is the primary causative agent of gastritis, gastric ulcers, duodenal ulcers, gastric cancer, and peripheral B-cell lymphoma. H. pylori eradication often fails due to elevated antibiotic resistance. However, no previous studies have thoroughly examined amoxicillin resistance. Here, the objective was to identify clinical strains of H. pylori with amoxicillin resistance and to analyze single-nucleotide polymorphisms (SNPs) associated with amoxicillin resistance. From March 2015 to June 2019, genotypic and phenotypic amoxicillin resistance was analyzed using an E-test and whole-genome sequencing (WGS). Analysis of 368 clinical strains confirmed amoxicillin resistance in 31 strains (resistance rate of 8.7%). The genomes were extracted from nine resistant (<0.125 mg/L) strains, and WGS was performed for genetic analysis. WGS analysis identified SNPs present in pbp1a, pbp2, nhaC, hofH, hofC, and hefC in all nine isolates. Some of these genes may be related to amoxicillin resistance. A total of six SNPs (A69V, V374L, S414R, T503I, A592D, and R435Q) were identified in PBP2 of H-8, the most resistant strain. We predict that these six SNPs are associated with high amoxicillin resistance. Amoxicillin resistance should be considered in the clinical setting for the treatment failure of H. pylori eradication.